National Cyber Security System Against the Cyber Attacks as threat to National Security - Taipe Dominguez, Daniel Ivan (2020)
The objective of the investigation was to analyze the National Cyber Security System against Cyber attacks as a threat to National Security; Of course, the study is intended to generate contributions that contribute to the solution of the problem presented; Regarding the methodology used, it can be noted that it has been descriptive, non-experimental descriptive correlational design, as results it is appreciated that it is necessary to seek to develop the strengthening of education, training and development of professional training lines of Cybersecurity specialists, in addition, awareness of cybersecurity should be established in all phases of the academic and professional training of the citizen.